Measurement of Electron Density and Temperature of Laser-Induced Copper Plasma - Naeem, M.A.; Iqbal, M.; Amin, N.; Musadiq, M.; Jamil, Y.; Cecil, F. (Asian Journal of Chemistry, 2012)
In present study, the Nd:YAG laser generated copper plasma has been evaluated as a function of distance (0.5-5 mm) at 17.6 and 88.6 mJ. The excitation temperature was determined using Boltzmann plot method of the transitions (4p P3/2 ® 3d 4s 2D5/2) at 510.34 nm (4d 2D3/2 ® 4p 2P1/2) at 515.12 nm, (4d 2D5/2 ® 4p 2P3/2) at 521.64, whereas electron number density was measured by Stark Broadening method. The spatial behaviour of the electron temperature and electron number density was measured at ambient air pressures. The electron temperature was found in the ranges from 16790-9090 K, while electron number density was 1.53 × 1017-1.85 × 1017 and 1.35 × 1017-1.87 × 1017 cm-3, respectively for 17.6 and 88.6 mJ energy. The relationship of electron number density and electron temperature found directly related to laser irradiation, while they were inverse to the distance form the target surface.